Detection of MicroRNAs in Dried Serum Blots - Patnaik, Santosh Kumar (2010)
We observed the preservation of microRNAs in unrefrigerated dried serum blots. Preservation was not adversely affected by drying or storing at 37, 45 or 60 °C instead of room temperature, but was harmed when blots were dried incompletely before storage. Preservation of microRNAs in serum was not diminished if instead of being kept frozen at −80 °C it was stored as dried blots at room temperature for five months or at 37 °C for four weeks. Dried blots can thus be a convenient and safer way to save, transport, and store serum for microRNA assays.